2013
DOI: 10.1007/s00464-013-2918-3
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic enucleation of esophageal leiomyoma in prone position and single lumen endotracheal intubation

Abstract: Thoracoscopic enucleation of esophageal leiomyoma is a feasible, simple, and safe procedure. Thoracoscopy in the prone position with CO2 insufflation allows the use of usual technique of intubation and also provides optimal operative field. The advantages of the thoracoscopic approach are less postoperative discomfort and lower risk of complications from open thoracotomy (especially pulmonary).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Video-assisted thoracoscopic surgery including thoracoscopic enucleation is described as a minimally invasive surgical procedure for esophageal SMT[ 5 ]. Performing thoracoscopic enucleation in the prone position, as compared with thoracotomy or thoracoscopic surgery in the decubitus position, has the advantages of adequate working area, minimal blood loss, and short postoperative stay[ 2 , 3 ]. However, the possibility of thoracoscopic enucleation may be limited by the tumor location and size.…”
Section: Discussionmentioning
confidence: 99%
“…Video-assisted thoracoscopic surgery including thoracoscopic enucleation is described as a minimally invasive surgical procedure for esophageal SMT[ 5 ]. Performing thoracoscopic enucleation in the prone position, as compared with thoracotomy or thoracoscopic surgery in the decubitus position, has the advantages of adequate working area, minimal blood loss, and short postoperative stay[ 2 , 3 ]. However, the possibility of thoracoscopic enucleation may be limited by the tumor location and size.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have recently investigated the prone position during minimally invasive esophagectomy for esophageal carcinoma, focusing on how it may contribute to suitable surgical visibility and the reduction of postoperative complications. Claus et al [ 11 ] reported the successful thoracoscopic enucleation of esophageal leiomyoma in the prone position with single-lumen endotracheal intubation in 10 patients, without any conversions [ 11 ]. We have also performed esophagectomy through a right thoracoscopy in the prone position, followed by laparoscopy and left cervicotomy in the supine position to treat upper thoracic esophageal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…There have been previous reports on thoracoscopic enucleation of esophageal leiomyoma in the prone position [ 10 , 11 , 12 ]. Additionally, we report the present case.…”
Section: Discussionmentioning
confidence: 99%